Neoantigen mRNA vaccines and A2A receptor antagonism: A strategy to enhance T cell immunity - Saber Imani; Parham Jabbarzadeh Kaboli; Ali Babaeizad; Mazaher Maghsoudloo (Human Vaccines & Immunotherapeutics)
Although neo-antigen mRNA vaccines are promising for personalized cancer therapy, their effectiveness is often limited by the immunosuppressive tumor microenvironment (TME). The adenosine A2A receptor (A2AR) inhibits dendritic cell (DC) function and weakens antitumor T cell responses through hypoxia-driven mechanisms within the TME. This review explores a novel strategy combining neo-antigen mRNA vaccines with A2AR antagonists (A2ARi). By targeting A2AR, this approach reduces TME-induced immunosuppression, enhances DC activation, and improves neo-antigen presentation. The review also discusses lipid nanoparticles (LNPs) to co-deliver A2ARi and mRNA vaccines, optimizing their effectiveness. The integration of neo-antigen mRNA-LNPs with A2ARi modulation offers a promising strategy to overcome immunosuppression, stimulate DC activation, and achieve precise anti-tumor responses with minimal off-target effects. This synergy represents significant progress in cancer immunotherapy, advancing the potential for personalized neoantigen therapies.